2021
DOI: 10.1098/rspa.2021.0271
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing a point source from diffusion fluxes to narrow windows in three dimensions

Abstract: We develop a computational approach to locate the source of a steady-state gradient of diffusing particles from the fluxes through narrow windows distributed either on the boundary of a three-dimensional half-space or on a sphere. This approach is based on solving the mixed boundary stationary diffusion equation with Neumann–Green’s function. The method of matched asymptotic expansions enables the computation of the probability fluxes. To explore the range of validity of this expansion, we develop a fast analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…In this section, we show how to extend this asymptotic analysis to obtain the full time-dependent arrival statistics. After applying the Laplace transform p(x; s) = R 1 t=0 e st p(x; t)dt to (2), we obtain the modified Helmholtz problem (18) We now discuss the inversion from Laplace space to physical time. One quantity of interest is the flux (3) through each of the receptors.…”
Section: Receptor Arrival Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we show how to extend this asymptotic analysis to obtain the full time-dependent arrival statistics. After applying the Laplace transform p(x; s) = R 1 t=0 e st p(x; t)dt to (2), we obtain the modified Helmholtz problem (18) We now discuss the inversion from Laplace space to physical time. One quantity of interest is the flux (3) through each of the receptors.…”
Section: Receptor Arrival Statisticsmentioning
confidence: 99%
“…1) and the distribution of arrivals across the set of receptors, known as the splitting probabilities [29], encodes information on the source location. In the scenario of planar di↵usion, or three dimension di↵usion to a spherical cell with surface receptors, Dobramysl and Holcman [17,18] demonstrated that a unique source location can be inferred from the splitting probabilities, provided the number of receptors is at least N = 3. Biological receptor numbers vary considerably between systems with examples including N ⇡ 10 4 in budding yeast [25] and N ⇡ 10 4 10 5 in lymphocytes [44].…”
mentioning
confidence: 99%
“…These facts render the computational effort quite prohibitive: Naive simulations become inefficient due to the very large excursions of Brownian trajectories before hitting targets of interest. We note however, that although the mean time is infinite, the splitting probability of hitting one of several windows is finite and thus estimating it can provide relevant information for many applications [28,27]. In this context, hybrid stochastic simulations circumnavigates these issues of naive Brownian simulations and avoids to simulate explicitly long trajectories with large excursions and thus it circumvents the need for an arbitrary cutoff distance for our infinite domain.…”
Section: Computing the Fluxes Of Brownian Particles To Small Targets ...mentioning
confidence: 99%
“…In analogy to equation 5.6, the sensitivity function for three windows in three dimensions is expressed as the maximum of the differences between the splitting probabilities computed from the fluxes [28] S 123 (x 0 ;…”
Section: Sensitivity Analysis In 3dmentioning
confidence: 99%
See 1 more Smart Citation